(3eSFdI SFd YfgG Hf GdMGLHs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3ChdgG (B:s
(3eSFdI SFd YfgG GdEeGe GdeMbb LeGd GdOjf Hf GdMGLH hgh HGdbGgQI ai QGHY LeGOi GdChd Sfg SJeGFg hKdGKg YTQ s
(3BNQgG (B:s
(3hJfajS GdcQH hdYdgG ai HdGO GdMLGR Ch eG CTHgg Jchf HgPg GdUaI hJhai GdCQZjGfi SfI KeGf hYTQhf hNeSeGFI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs